PEMAHAMAN KONSEP DASAR MATEMATIKA PADA MAHASISWA PRODI PENDIDIKAN MATEMATIKA - Bina, Nuraini Sri; Rusmini, Rusmini; Lubis, Atipah (Program Studi Pendidikan Matematika, Fakultas Keguruan Dan Ilmu Pendidikan, Universitas Alwashliyah Medan, 2025)
Understanding the basic concepts of mathematics is an important foundation for students of the Mathematics Education Study Program to be able to become competent educators in the future. However, there are still many students who have difficulty mastering these concepts. This study aims to determine the level of understanding of basic mathematical concepts of fifth-semester students and identify the factors that affect them. The research used a descriptive survey method with an instrument in the form of a questionnaire distributed to 12 students. The data collected was analyzed descriptively to illustrate the level of understanding of basic concepts and their relevance to daily life. The survey results show that most students have a fairly good understanding of basic mathematical concepts, but there are still challenges in terms of applying concepts, learning independence, and confidence in facing difficult material. The conclusion of this study is that a more contextual learning approach is needed, the provision of additional support such as tutorials or remedial learning, and a conducive learning environment to improve students' overall understanding.